Free-breathing fat and R2∗ quantification in the liver using a stack-of-stars multi-echo acquisition with respiratory-resolved model-based reconstruction - Schneider, Manuel; Benkert, Thomas; Solomon, Eddy; Nickel, Dominik; Fenchel, Matthias; Kiefer, Berthold; Maier, Andreas; Chandarana, Hersh; Block, Kai Tobias (Magnetic Resonance in Medicine, 2020)
Purpose: To develop a free-breathing hepatic fat and (Formula presented.) quantification method by extending a previously described stack-of-stars model-based fat-water separation technique with additional modeling of the transverse relaxation rate (Formula presented.) . Methods: The proposed technique combines motion-robust radial sampling using a stack-of-stars bipolar multi-echo 3D GRE acquisition with iterative model-based fat-water separation. Parallel-Imaging and Compressed-Sensing principles are incorporated through modeling of the coil-sensitivity profiles and enforcement of total-variation (TV) sparsity on estimated water, fat, and (Formula presented.) parameter maps. Water and fat signals are used to estimate the confounder-corrected proton-density fat fraction (PDFF). Two strategies for handling respiratory motion are described: motion-averaged and motion-resolved reconstruction. Both techniques were evaluated in patients (n = 14) undergoing a hepatobiliary research protocol at 3T. PDFF and (Formula presented.) parameter maps were compared to a breath-holding Cartesian reference approach. Results: Linear regression analyses demonstrated strong (r > 0.96) and significant (P ≪.01) correlations between radial and Cartesian PDFF measurements for both the motion-averaged reconstruction (slope: 0.90; intercept: 0.07%) and the motion-resolved reconstruction (slope: 0.90; intercept: 0.11%). The motion-averaged technique overestimated hepatic (Formula presented.) values (slope: 0.35; intercept: 30.2 1/s) compared to the Cartesian reference. However, performing a respiratory-resolved reconstruction led to better (Formula presented.) value consistency (slope: 0.77; intercept: 7.5 1/s). Conclusions: The proposed techniques are promising alternatives to conventional Cartesian imaging for fat and (Formula presented.) quantification in patients with limited breath-holding capabilities. For accurate (Formula presented.) estimation, respiratory-resolved reconstruction should be used.
CRIS-Team Scopus Importer:2020-04-28
Keywords: compressed sensing; free-breathing fat/ R2∗ quantification; multi-echo 3D stack-of-stars GRE; nonalcoholic fatty liver disease; radial sampling; respiratory motion-resolved reconstruction